IMPLEMENTASI METODE AT-TARTIL DALAM PEMBELAJARAN QIRO’ATUL QUR’AN KELAS 3 DI MI MUJAHIDIN PARIMONO JOMBANG - Vivi Afbrifani; Izzah Is'adah (Prodi PGMI Institut Agama Islam Bani Fattah Jombang, 2022)
The Qur'an is the holy book of Muslims which was revealed to the Prophet Muhammad SAW. through the angel Gabriel. Seeing the low interest in learning to read the Qur'an in this modern era, KH. Imam Shafi'I, KH. Fahruddin Sholih, and KH. Masykur Idris tries to make practical learning, CBSA (an active way of learning for students), and uses drills. With a relaxed but organized learning system, it is hoped that it can encourage the spirit of learning to read the Qur'an in this modern era. Based on the statement above, the authors are encouraged to conduct research on